Some preliminary results on analysis of concrete flexural members with hybrid reinforcements - Leung, Hau Y. (Journal of Civil Engineering and Management, 2003)
It is generally accepted that conventional steel reinforced concrete (RC) flexural members usually fails in a ductile mode with low load-carrying capacity. In contrast, recent introduction of fibre-reinforced-polymer (FRP) rods into RC beams gives rise to a higher ultimate load but it lacks ductility. It is anticipated that a hybrid combination of conventional steel rebars and novel FRP rods as reinforcing materials in concrete beam can provide a strong and ductile beam characteristics. Prior to the experimental verifications, a preliminary analytical study is carried out. The analytical model describes some features of the flexural behaviour of concrete members reinforced with hybrid reinforcing materials. The model implementation is based on the use of the true stress-strain relationships for plain concrete, steel rebar and FRP rod. The main variable considered in present study is the arrangement of steel rebars and FRP rods. This paper presents some particular findings from the model. Most results are also compared with that of concrete beam reinforced only with steel rebars.First Published Online: 26 Jul 2012